Study of a lytic bacteriophage as a tool for the control of Salmonella Gallinarum in layer poultry - Ortiz, Xoana Pamela (2024)
One of the leading diseases affecting laying poultry in Argentina is fowl typhoid, caused by the pathogen Salmonella enterica serovar Gallinarum (S. Gallinarum). Although this disease was eradicated from industrial hatcheries in several developed countries, it is still present in commercial farms in Latin America, causing substantial economic losses due to high mortality rates, limited production of quality eggs, high veterinary costs, and the need to renovate infected facilities. To develop a new S. Gallinarum biocontrol method, in the present study, we characterized a bacteriophage in terms of host specificity, growth kinetics, and stability under different environmental conditions. The phage could infect an ample range of bacterial hosts and had no lytic activity against the vaccine strain 9R. Moreover, the phage was stable at pH 3, chloroform presence did not significantly reduce its titer, and its activity was not affected by antibiotics or various chemical agents often used in aviculture. Application of a phage suspension on S. Gallinarum-contaminated surfaces resulted in a significant reduction of bacterial load (p < 0.05). These results show that lytic bacteriophages such as the one studied here are innovative alternatives with potential applications to control S. Gallinarum in laying poultry farms.